Platelet count/spleen diameter ratio: analysis of its capacity as a predictor of the existence of esophageal varices - Mattos,Ângelo Zambam de (2010)
CONTEXT: Upper gastrointestinal bleeding associated to esophageal varices is the most dramatic complication of cirrhosis. It is recommended screening every cirrhotic for esophageal varices with endoscopy. OBJECTIVES: To evaluate the capacity of the platelet count/spleen diameter ratio in non-invasively predicting esophageal varices in a population of cirrhotics originated in an independent center from the one in which it was developed. METHODS: The study included patients from the ambulatory care clinic of cirrhosis of a Brazilian hospital and studied platelet count, spleen diameter and presence of esophageal varices, as well as Child and MELD scores. It used a cutoff value of 909 for the platelet count/spleen diameter ratio, as previously published. A sample of 139 patients was needed to grant results a 95% confidence level. RESULTS: The study included 164 cirrhotics, 56.7% male, with a mean age of 56.6 ± 11.6 years. In the univariate analysis, platelet count, spleen diameter, presence of ascites, Child and MELD scores and the platelet count/spleen diameter ratio were related to esophageal varices (P<0.05). The platelet count/spleen diameter ratio had sensitivity of 77.5% (95% CI = 0.700-0.850), specificity of 45.5% (95% CI = 0.307-0.602), positive predictive value of 79.5% (95% CI = 0.722-0.868), negative predictive value of 42.6% (95% CI = 0.284-0.567) and accuracy of 68.9% (95% CI = 0.618-0.760). In the multivariate analysis, platelet count was the only variable which related to esophageal varices (P<0.05). CONCLUSION: Platelet count/ spleen diameter ratio is not adequate to predict esophageal varices in cirrhotics.